Recent Advances in Manufacturing Processes and Systems Select Proceedings of RAM 2021 - Dave, Harshit K.; Dixit, Uday Shanker; Nedelcu, Dumitru; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents select proceedings of 2nd International Conference on Recent Advances in Manufacturing (RAM 2021). The book provides insights into the current research trends and development in manufacturing processes. The topics covered include conventional and nonconventional manufacturing processes, micro and nano manufacturing processes, chemical and biochemical manufacturing, additive manufacturing, smart manufacturing, and sustainable and energy-efficient manufacturing. The contributions presented here are intended to stimulate new research directions in the manufacturing domain. This book will be useful for the beginners, researchers and professionals working in the area of industrial and production engineering and allied fields.
A study on Residual Stress Distribution in Welded Joint of P91 and SS304H Steel Plate -- A Methodology for Data-driven Estimation of Forging Load -- A Preliminary Investigation on Different Tool Wears in Sustainable Electrical Discharge Machining of Ti-6Al-4V -- A Review on Microstructure and Mechanical Properties of L-PBF 17-4PH and 15-5PH SS -- A Review on Twin Wire Arc Additive Manufacturing of Metals and Alloys: Microstructure and Mechanical Properties -- A State-of-the-Art Review of Additively Manufactured Auxetic Structures -- ABS-Fly Ash Composite Filaments for Fused Deposition Modeling -- A Comparative Study and Optimization of Parameters of Turning UD-GFRP in Dry, Wet and Cryogenic Condition by using PCD tool with Taguchi Method -- An Experimental Investigation on Effect of Process Parameters on Microstructure and Mechanical Properties of Spheroidal Graphite Cast Iron -- An Insight of Compacted Graphite Iron (CGI) Characteristics and its Production: A Review.
Keywords: Industrial engineering; Production engineering; Manufactures; Automation; Industrial and Production Engineering; Machines, Tools, Processes; Industrial Automation; Manufacturing processes -- Congresses; Materials science -- Congresses